2018
DOI: 10.3823/821
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular characterization of metallo-β-lactamases (MBLs) among Acinetobacter baumannii isolates from cancer patients

Abstract: Background: During the last decade, the prevalence of carbapenem-resistant infection associated with multidrug resistant (MDR) Acinetobacter baumanniiin patients has been continuously increasing.  This prospective study aimed to determine the occurrence and molecular characterization of metallo-β-lactamases (MBLs) and carbapenem hydrolyzing oxacillinases among A. baumannii isolates from cancer patients over a period of 6-month. Methods:Antimicrobial susceptibility profile of 70 randomly collected A. baum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In this study, bla NDM‐1 was identified in 10.4% of isolates; all of which were classified as XDR. A previous local study from 2016 has reported a higher prevalence (19%) of bla NDM‐1 in A. baumannii isolated from cancer patients 42 . In addition, many studies from Middle Eastern countries documented the detection of this gene, for example in Lebanon, 43 Iran, 44,45 Saudi Arabia 46 and Egypt 47 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, bla NDM‐1 was identified in 10.4% of isolates; all of which were classified as XDR. A previous local study from 2016 has reported a higher prevalence (19%) of bla NDM‐1 in A. baumannii isolated from cancer patients 42 . In addition, many studies from Middle Eastern countries documented the detection of this gene, for example in Lebanon, 43 Iran, 44,45 Saudi Arabia 46 and Egypt 47 .…”
Section: Discussionmentioning
confidence: 96%
“…A previous local study from 2016 has reported a higher prevalence (19%) of bla NDM-1 in A. baumannii isolated from cancer patients. 42 In addition, many studies from Middle…”
Section: Discussionmentioning
confidence: 99%